Microinverter Topology based Single-stage Grid-connected Photovoltaic System: A Review - A. Razi; M. Nabil Hidayat; M. N. Seroji (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper discussed the topology development of a single-stage microinverter in grid-connected PV system. In general, the microinverter topologies can be categorized into four type of topologies:          1) Flyback inverter, 2) Double-boost inverter, 3) Derived zeta-cuk configuration and 4) Buck-boost inverter. Flyback configuration is widely used for single-stage microinverter which offers protection between solar panel and utility grid. However due to the bulkiness of the transformer, new arrangement circuit employ the Half-Bridge topology with film capacitor and microcontroller provide a good room for research and future developments to obtain greater efficiency and compact design of single-stage microinverter grid-connected PV system. Plus, there are several characteristics need to be taken care for future development of the microinverter technology.